MATHEMATICS TEACHERS’ BELIEF RELATED TO CONTINUING PROFESSIONAL DEVELOPMENT (CPD) - Merliza, Pika; Ralmugiz, Uke (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
The study aims to describe the number of JHS mathematics teachers in Bandar Lampung, Lampung, Indonesia toward belief related to CPD activities. This type of study was a mixed method (or quantitative-qualitative) using explanatory sequential strategy. The subjects were 181 Junior High Schoohl (JHS) mathematics teachers in Bandar Lampung, Lampung, Indonesia who have already become civil servants. Meanwhile, the quantitative research sample was 63 JHS mathematics teachers in Bandar Lampung, Lampung, Indonesia established using stratified random sampling technique based on teachers’ worked experiences, then chosen on each level with proportional random sampling. Furthermore, the qualitative sample was eight teachers for the case study which was decided by purposive sampling technique. The research instrument consisted of questionnaire and interview list. Data analysis techniques was conducted using categorized into 5 groups: really belief, belief, quite belief, less of belief, and unbelief. The result of research show that JHS mathematics teachers’ belief toward CPD activities is in the belief category. Then, based on teachers’ experiences related to CPD belief is founded that there is no differences on their belief.